2015
DOI: 10.5530/jyp.2015.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Consistency between Causality Assessments Obtained With Various Scales and Their Agreement for Adverse Drug Events Reported in Pediatric Population

Abstract: Objective: The goal of this study was to examine correlation between various causality assessments scales and their agreement in reporting ADRs in children. Methods: All hospitalized pediatric patients were followed up for adverse drug reaction in a single pediatric unit for one year. We compared the WHO, Naranjo, CIOMS/RUCAM and French causality assessment scales in 36 identified ADRs in pediatric ward during 2012. The agreement between obtained causality assessments were analyzed by Cohen's Kappa (K) statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The study shows that incidence rate of ADRs was found to be more for males when compared to females. Our findings were similar to the study conducted by Devang Ashwinkumar Rana et al [3] and Dilip et al [4]. The study also showed that the incidence rate for geriatrics to be higher than adults and pediatrics.…”
Section: Discussionsupporting
confidence: 92%
“…The study shows that incidence rate of ADRs was found to be more for males when compared to females. Our findings were similar to the study conducted by Devang Ashwinkumar Rana et al [3] and Dilip et al [4]. The study also showed that the incidence rate for geriatrics to be higher than adults and pediatrics.…”
Section: Discussionsupporting
confidence: 92%
“…Rana et al . [ 14 ] also found poor agreement (Cohen's κ =0.014) between the WHO-UMC scale and the Naranjo algorithm. In this study, only 36 ADRs were analyzed, all belonging to the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Cohen's kappa coe cient (κ) statistical test, demonstrated that there was no agreement between the WHO and Naranjo Causality Scales. Studies conducted by other research groups also yielded similar results, with the kappa coe cient statistical test demonstrating low agreement between the WHO and Naranjo Causality Scales [33,41,42]. Given these ndings, developing a gold standard evaluation scale is essential to improve the quality and reliability of future causality assessments.…”
Section: Variations In Resultsmentioning
confidence: 63%